Financovaní projektů z fondů EU - Butek, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Cielom diplomovej práce je návrh na vybudovanie lanového centra v konkrétnej lokalite za využitia podpory fondov EÚ. Prvá časť je zameraná na predstavenie projektu, analýzu prostredia a podmienok v ktorých bude projekt realizovaný. V druhej časti sú predostreté návrhy realizácie projektu a ich následné zhodnotenie.

The aim of this thesis is a concept of a high rope centre in a particular location with support of EU funds. The first part of this thesis gives an overview at the project and presents an analysis of the environment and the conditions in which the project will be realized. The concepts of the project realization and the evaluation of the proposed concepts are presented in the second part.
Financing of Projects from EU Funds
Keywords: európske fondy; Program cezhraničnej spolupráce; neziskové organizácie; lanové aktivity; podnikatelský plán; European union funds; Cross-border cooperation programme; non-profit organizations; rope activities; business plan